"Supporting nursing, midwifery and allied health professional students to raise concerns with the quality of care: A review of the research literature". (October 2017) - Milligan, Frank; Wareing, Mark; Preston-Shoot, Michael; Pappas, Yannis; Randhawa, Gurch; Bhandol, Janine
Abstract: Background: This article reports aspects of a systematic literature review commissioned by the UK Council of Deans of Health. The review collated and analysed UK and international literature on pre-registration healthcare students raising concerns with poor quality care. The research found in that review is summarised here. Objective: To review research on healthcare students raising concerns with regard to the quality of practice published from 2009 to the present. Data Sources: In addition to grey literature and Google Scholar a search was completed of the CINAHL, Medline, ERIC, BEI, ASSIA, PsychInfo, British Nursing Index, Education Research Complete databases. Review Method: Sandelowski and Barroso's (2007) method of metasynthesis was used to screen and analyse the research literature. The review covered students from nursing, midwifery, health visiting, paramedic science, operating department practice, physiotherapy, chiropody, podiatry, speech and language therapy, orthoptist, occupational therapy, orthotist, prosthetist, radiography, dietitian, and music and art therapy. Results: Twenty three research studies were analysed. Most of the research relates to nursing students with physiotherapy being the next most studied group. Students often express a desire to report concerns, but factors such as the potential negative impact on assessment of their practice hinders reporting. There was a lack of evidence on how, when and to whom students should report. The most commonly used research approach found utilised vignettes asking students to anticipate how they would report. Conclusions: Raising a concern with the quality of practice carries an emotional burden for the student as it may lead to sanctions from staff. Further research is required into the experiences of students to further understand the mechanisms that would enhance reporting and support them in the reporting process. Highlights: Students are expected to report concerns with the quality of care. Reporting can adversely affect student assessment grades. Little is known of the lived experience of students that report.